PENGARUH KUALITAS PRODUK, HARGA, MEREK DAN SALURAN DISTRIBUSI TERHADAP VOLUME PENJUALAN PADA PT. GELANG GEMILANG JAYA BELLA SPRING BED SEMARANG - Untung Widodo (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2020)
This research was conducted in order to test how much influence product quality, price and brand to the volume of sales at PT. Gemilang Jaya Bella bracelets Spring Bed Semarang. Independent variables include variable product quality, price and brand while the dependent variable is the volume of sales.In determining the data to be studied sampling technique used is the census. Census is a sampling technique when all members of the population used as a sample .. Respondents were selected is the consumer stores PT. Gemilang Jaya Bella bracelets Spring Bed Semarang. Thus obtained sample was 50 respondents. Data analysis methods used to perform hypothesis testing is multiple linear regression analysis.Based on the results of research that has been conducted on all data obtained, the importance of the research that 1). There is a positive and significant effect of the variable quality of the product (X1) to sales volume (Y). 2). There is a positive and significant impact on price variable (X2) to sales volume (Y). 3). There is a positive and significant impact on brand variables (X3) to sales volume (Y). 4). There is a positive and significant effect of the variable distribution channels (X4) to sales volume (Y)